Complicaciones intraoperatorias de la cirugía urológica en el anciano. - Resel, Luis; Gómez Vegas, Ángel; Silmi Moyano, A.; Begara Morillas, F.; Blázquez Izquierdo, J. (Clínicas Urológicas de la Complutense, 1993)
Sin resumen